Understanding Violence Against Women in the Caribbean Through an Exploration of Men's Perspectives - Joseph, Debra D. (Violence against women, 2023)
Qualitative research with 60 males (16–80 years) from two Caribbean countries was carried out to explore men’s perspectives on domestic violence (DV). An inductive latent/thematic approach to data analysis supported by analytic software led to five key domains being identified: (1) meanings of violence; (2) patrinormative culture; (3) normalization of violence; (4) male victimization; and (5) blame attribution and empathy. Patriarchal values, together with childhood exposure to violence, were found to reduce empathic capacity and contribute to the normalization of DV. In addition, the minimization of male victimization and the lack of behavior-change support services for men were identified as contributory factors.